Longitudinal Changes in Size and Composition of Carotid Artery Plaques Using Ultrasound: Adaptation and Validation of Methods (Inter- and Intraobserver Variability). Issue 4 (December 2014) - Bjornsdottir, Gudlaug; Sigurdsson, Sigurdur; Sturlaugsdottir, Ran; Gudmundsdottir, Agnes; Eiriksdottir, Gudny; Thorsson, Bolli; Aspelund, Thor; Gustavsson, Tomas; Launer, Lenore J.; Harris, Tamara B.; Gudnason, Vilmundur
Introduction: B-mode ultrasonography of the carotid arteries enables quantitative measurements of atherosclerotic plaque area and composition assessed as grayscale median (GSM). The purpose of this study was to set up a standardized ultrasound protocol to measure longitudinal changes in plaque area and composition and to determine the intra- and interobserver variability of the measurements in a longitudinal population based study, the Age Gene/Environment Susceptibility Reykjavik study. Method: A total of 219 participants from the Age Gene/Environment Susceptibility Reykjavik study (76 ± 6 years old, 36% males) underwent 2-dimensional, B-mode ultrasound examination of the carotid arteries approximately 5 years apart for a longitudinal assessment of plaque area and composition. Standardized protocol was used to acquire comparable images from both visits. Ultrasound was performed bilaterally on the common carotid artery, internal carotid artery, and bifurcation. An image analysis program was modified and adapted for a longitudinal assessment of plaque area and plaque composition by GSM. Twenty-five subjects were selected from the group of 219 for intra- and interobserver variability assessment. Results: Intraobserver variability for plaque area ranged from 12.10 to 18.63% and 0.89 to 0.96 for coefficient of variation and correlation (r), respectively, for plaque GSM ranged from 7.77 to 8.04% and 0.86 to 0.90. Interobserver variability for plaque area was 23.29% and 0.81 and 8.55% and 0.87 for plaque GSM. Conclusion: The results from this study show that ultrasound can be used consistently for assessment of changes in plaque area and GSM over time. This can be achieved by proper training of ultrasound sonographers and by applying and following strict image acquisition and image analysis protocols.